Marine Tourism Suitability Index in the Padang Beach Tourism Area, West Sumatra - Ishlahul Fikri; Etty Riani; Syahril Nedi (Jurnal Penelitian Pendidikan IPA, 2024)
This research was conducted to determine the suitability of marine tourism conditions for the beach recreation category in order to ensure the sustainability of marine tourism, as Kawasan Wisata Pantai Padang is frequently visited by both domestic and international tourists. This can increase anthropogenic activities in the area and lead to a significant amount of marine debris, especially plastic waste, thus potentially compromising the aesthetic value of the tourist beach and even causing environmental pollution and negative impacts on humans. The collection of IKW data employs the purposive sampling method. The observation stations are divided into 8, each observation station consists of an area with different characteristics related to human activities such as densely populated areas, river estuaries, tourist areas, and sparsely populated areas. The determination of the suitability index for beach recreational marine tourism is carried out using a suitability matrix analysis, considering 10 parameters such as Beach Type, Substrate Material, Water Depth, Water Clarity, Current Velocity, Beach Slope, Coastal Land Cover, Hazardous Biota, and Freshwater Availability. The condition of the suitability index parameters for recreational beaches in the Padang Beach Tourism Area at stations 2, 3, 4, and 5 obtains a value of 2.56, indicating that they fall into the category of highly suitable (total score greater than 2.5). Furthermore, at stations 1 and 6, the obtained values are 2.095, classifying them as suitable (total score slightly less than 2.5), and stations 7 and 8 achieve a value of 1.89, categorizing them as not suitable (total score less than 2.0).The results indicate that overall, the Padang Beach Tourism Area falls within the category of highly suitable for beach recreational tourism and can be further developed in its management.